A CFD model development and performance investigation of frost free refrigerator with nanoparticles suspended in the lubricant - Haque, Muhammad Ehteshamul (2019)
In a refrigerator, airflow and temperature distribution along with the properties of the lubricating oil defines its efficiency and performance. The purpose of this work is to develop a numerical model to predict the airflow and temperature inside the refrigerated space and use nanoparticles in the compressor lubricating oil to improve the efficiency of the refrigerating system. The present research focuses to improve the performance and efficiency of the refrigerator through the analysis by CFD and nanotechnology. The objective is to develop a CFD model for airflow and temperature distribution inside the refrigerator and validated it with experimental results. The model is then used for parametric study to modify the inside geometry of the refrigerator to improve better airflow and temperature distribution. To improve the cyclic efficiency of the refrigerator Nano-particles are added into the compressor lubricant to improve the lubricity of Polyol ester oil (POE), thereby improving the performance of the refrigerator. In this research work, CFD model has been developed for a domestic no-frost refrigerator. The conservation equations of energy mass and momentum are solved by using Finite Volume Method (FVM) in an environment of three-dimensional unstructured mesh. Experiments were conducted on a no-frost domestic refrigerator to compare and validate the results of the CFD model. Nano particles when added to the lubricating oil is called Nano-lubricant. In the present study, three nanoparticles namely Al2O3, TiO2 and SiO2 have been added to the lubricant oil of a domestic refrigerator and experiments have been performed to determine the enhancement in the performance of the refrigerator. A CFD model for the selected refrigerator has been developed in Ansys software. This CFD model has been validated by experimental results. A comparison of CFD model and experimental results of surface temperature in freezer and refrigerator compartment are within the acceptable range of 5% difference. In the freezer compartment the difference in temperature on a vertical line at the center of freezer as predict by the CFD model and experiment is less than one percent. Similarly, the temperature difference, as measured by experiment and predicted by the CFD model, on a central vertical line inside the refrigerator compartment, is less than three percent. The result of the parametric study by using the developed CFD model showed improvement in the temperature distribution inside the refrigerator compartment. Through this research work, it is established that CFD can be used successfully to model the airflow and temperature distribution inside the refrigerator. The results of experiments with nanoparticles suspended in the lubricant oil of the compressor showed better performance of the refrigerator as compared to pure Polyol Easter (POE) oil system. The energy consumption of 0.05% SiO2 nanolubricant is 9.4% less than pure POE oil system. Similarly, the energy consumption of compressor with 0.1% TiO2 nanoparticles is 6.84% lower than the pure POE oil system. COP of the refrigerator increased by 29% when 0.1% SiO2 nanoparticle was added to the compressor lubricant. Therefore, the addition of nanoparticles in the refrigerator system has very good potential to improve the energy consumption and COP of the unit.